ENVIRONMENTAL SUPERVISION IN PALM OIL INDUSTRY WASTE MANAGEMENT IN PELALAWAN REGENCY - Nahrin Zakiyah; Rahmadani Yusran (PT. Radja Intercontinental Publishing, 2026)
Environmental monitoring is a crucial instrument for ensuring industrial compliance with waste management, particularly in areas with high palm oil industry activity. This study aims to analyze environmental monitoring in palm oil industrial waste management in Pelalawan Regency. The study employed a descriptive qualitative approach involving twelve informants from the Pelalawan Regency Environmental Agency, palm oil companies, and communities surrounding the industrial area. Data were collected through in-depth interviews and documentation, tested through source triangulation, and analyzed interactively through data reduction, data presentation, and conclusion drawing. The results indicate that environmental monitoring is implemented through a series of preventive and repressive measures that include company guidance, administrative compliance checks, land application , field inspections, public complaint handling, and corrective actions. These two forms of monitoring do not occur separately but are interconnected in the process of maintaining company compliance. This study found that the main problem with monitoring lies not primarily in the lack of instruments, but in the inconsistent interconnection between monitoring instruments. Limited inspection frequency impacts the verification and early detection functions, some community information is not yet connected to the government monitoring system, and the dominance of the coaching approach requires more consistent follow-up monitoring. This study emphasizes the importance of integrating compliance information, inspection results, corrective action history, and public complaints to strengthen ongoing environmental oversight.